African Surrealism in Federico García Lorca’s Poeta en Nueva York:: A Study of Racial Identity and Social Critique - Chaosakun, Narut (Journal of Letters, 2025)
This article presents a comprehensive analysis of Federico García Lorca’s surrealist poetry concerning the Black ethnic group, focusing specifically on the poems “Norma y paraíso de los negros” and “El rey de Harlem” from his collection Poeta en Nueva York. The study employs the perspective of Afrosurrealism, an artistic and literary movement that emerged later in the United States, integrating an understanding of the distinctive surrealist symbols and “poetic logic” characteristic of Lorca’s surrealism. This analysis elucidates the intersection between the contextual background and the underlying ideas of the two poems, derived from Lorca’s personal experiences, and the Afrosurrealism concepts related to racial identity and the experiences of African Americans in New York. Furthermore, the study highlights how Lorca employs surreal symbols to critique the social injustices faced by Black individuals and to revive a consciousness of Black identity, thereby challenging the oppressive and intoxicating white civilization that obscures the cultural roots of Black people.